2022
DOI: 10.3390/fire5050166
|View full text |Cite
|
Sign up to set email alerts
|

Wildfire Risk Levels at the Local Scale: Assessing the Relative Influence of Hazard, Exposure, and Social Vulnerability

Abstract: Wildfire risk assessment provides important tools to fire management, by analysing and aggregating information regarding multiple, interactive dimensions. The three main risk dimensions hazard, exposure and vulnerability, the latter considered in its social dimension, were quantified separately at the local scale for 972 civil parishes in central mainland Portugal and integrated into a wildfire risk index. The importance of each component in the level of risk varied, as assessed by a cluster analysis that esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 59 publications
3
15
0
Order By: Relevance
“…Full agreement is also found with [16], who designed a complete and detailed FR map for mainland Portugal, which was accepted by the Portuguese fire authority Agency for Integrated Rural Fire Management. Our focus on the most hazardous FR comes from the recent 2017 extreme wildfires events which had extensive impacts, including over 100 casualties [28]. We note that although both assessed ecosystem services are priorities, FR should be significantly valued, reflecting all direct implications for society and the environment.…”
Section: Methodological Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Full agreement is also found with [16], who designed a complete and detailed FR map for mainland Portugal, which was accepted by the Portuguese fire authority Agency for Integrated Rural Fire Management. Our focus on the most hazardous FR comes from the recent 2017 extreme wildfires events which had extensive impacts, including over 100 casualties [28]. We note that although both assessed ecosystem services are priorities, FR should be significantly valued, reflecting all direct implications for society and the environment.…”
Section: Methodological Prospectsmentioning
confidence: 99%
“…Land-use is the only driver directly changeable to address fire protection and carbon storage, while other drivers cannot or can only at the global scale (e.g topography, climate, weather) [16,[27][28][29][30][31].…”
mentioning
confidence: 99%
“…Many studies, including those by Elia et al [4], Mostafa et al [16] Hong et al [17], Bergonse et al [18], Sinha et al [19], and Zhang et al [20], have used road density and distance in wildfire mapping and modeling as independent variables. For example, Hong et al [17] found that the spatial distribution of wildfire susceptibility is correlated to landscape attributes that have been shaped by residential areas and road networks in Huichang County, China.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hong et al [17] found that the spatial distribution of wildfire susceptibility is correlated to landscape attributes that have been shaped by residential areas and road networks in Huichang County, China. Bergonse et al [18] showed that the enhancement of road density contributed to improved evacuation during wildfire disasters in Portugal. Sinha et al [19] found that the forest road network, as one of the anthropogenic indicators, is a contributing factor to more than 60% of wildfire occurrence in the Western Ghats and the Kedarnath Wildlife Sanctuary in the Himalayas.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have focused their analysis on improving fire prediction and assessment, using machine learning techniques, e.g., [26], and on the identification of the areas that are more vulnerable to fire occurrences. The latter usually relies on meteorological variables and fire danger ratings [27], or on their combination with morphological factors, such as elevation, slope angle, population density, fire's exposition, and land cover [28][29][30][31]. These studies strongly improved the knowledge of fire regimes in Portugal and showed where the responsible authorities should act in order to mitigate the fire risk in certain regions which are highly exposed to fire.…”
Section: Introductionmentioning
confidence: 99%